Alfredo Conti - Hayakawa Casas, José (2025)
Architect specializing in heritage conservation from the University of Buenos Aires. Honorary Doctorate from the Autonomous University of Zacatecas. Professor at the National University of La Plata; he teaches courses and seminars at other universities in Argentina and Latin America and at the UNESCO Chair of Cultural Tourism (Buenos Aires). Emeritus Advisor to the National Commission of Monuments, Sites and Historic Properties, Argentina. President of the International Council on Monuments and Sites (ICOMOS) Argentina from 2006 to 2012 and Vice President of ICOMOS International from 2010 to 2017. Since 2000, he has served as an ICOMOS expert on advisory, evaluation, and monitoring missions for World Heritage sites. He has collaborated with institutions such as the Getty Conservation Institute, the Organization of World Heritage Cities, the World Monuments Fund, and the Regional World Heritage Institute in Zacatecas, and has provided consulting services in various countries in the Americas, Europe, and Asia. He is a UNESCO consultant on cultural heritage projects.